Frequency of HBsAg/anti-HCV seropositivity and its relationship with risk factors in extrahepatic malignancies - Abdullah OKAN; İnci OKAN and Servet AKAR and Ender ELLİDOKUZ and Hale AKBAYLAR and Ramazan ŞEKEROĞLU and Fadime AKMAN and Fatma BACAKSIZ and Ethem TANKURT and İlkay ŞİMŞEK and; l. (Turkish Journal of Gastroenterology, 2019)
-